P-125 Adalimumab Serum Concentrations or Anti-Drug Antibodies Do Not Influence Fatigue in Patients with Crohn's Disease. (February 2017) - Karlsen, Lars Normann; Carlsen, Arne; Omdal, Roald; Aabakken, Lars; Bolstad, Nils; Lundin, Knut; Grimstad, Tore
Abstract : Background: Fatigue is a common phenomenon in patients with inflammatory bowel diseases (IBD). Biological treatment alleviates fatigue in a number of diseases, but it is unclear whether different serum concentrations of the drug or development of anti-drug antibodies influence fatigue. Methods: In a cohort of adult patients with Crohn's disease, who had received at least 3 doses of adalimumab, we investigated whether serum drug concentration or anti-drug antibodies influenced severity of fatigue. Fatigue was measured by the Fatigue Severity Scale (FSS) and the fatigue Visual Analogue Scale (fVAS), and mood assessed with the subscale of the Hospital Anxiety and Depression Scale (HADS-D). Serum drug concentrations and anti-drug antibodies were measured using an in-house assay automated on the AutoDELPHIA immunoassay platform at Oslo University Hospital. Therapeutic serum drug concentration for adalimumab was defined as ≥5 mg/L. Clinical significant fatigue was defined as fVAS scores ≥50 mm or FSS scores ≥4. Depression was defined as HADS-D scores ≥8. Results: In total, 103 patients were eligible for inclusion. Serum drug concentration data were available from 101 (98%), fVAS data from 87 (84.4%), FSS data from 75 (72.8%) and HADS-D data from 87 (84.4%) of the patients. Median (range) age was 35 (16–78) years, and 47.5% were men. Disease duration was 9 (1–36) years, and treatment duration 32 (2–112) months. Median adalimumab serum drug concentration was 6.9 (0–24.6) mg/L, 19 (18.8%) had a serum drug concentration below therapeutic cut-off. Thirty-five (46.7%) patients had FSS scores ≥4, 28 (32.2%) fVAS scores ≥50 and 8 (9.2%) HADS-D scores above cut-off. In the 2 groups of patients with serum drug concentrations below and above 5 mg/L, median FSS scores were 3.7 (1–7) versus 3.3 (1–6), P = 0.95; fVAS 38.0 (2–86) versus 24.0 (1–80), P = 0.35; and HADS-D scores 2.0 (0–11) versus 2.5 (0–16), P = 0.58. Six (6.9%) patients had anti-drug antibodies, all with serum drug concentration < 5 mg/L. In the anti-drug antibodies positive versus negative group the median FSS score was 3.2 versus 3.3, P = 0.95, and for fVAS scores 23.5 versus 25.0, P = 0.71. Conclusions: In patients with Crohn's disease, fatigue and mood are not influenced by serum concentrations of adalimumab, nor by presence of anti-drug antibodies.